The Influence of Entertainment Tax Receiving and Advertising Tax on Regional Original Income - Zulia Hanum (AIBPM Publisher, 2022)
The purpose of this study is to investigate the effect of entertainment tax revenue on the local income of Serdang Deli Regency, to determine the Effect of Advertising Tax Revenue on Deli Serdang Regency's Original Regional Revenue, to determine the effect of entertainment tax revenue and advertising tax on the local income of Serdang Deli. The research approach used in this research is quantitative associative with documentation technique. In this study is quantified by the documentation technique. The data sources for this study are reports of the realization of domestic tax revenues and entertainment tax and advertising tax revenues from 2016 to 2020. The data analysis used is descriptive statistics, multiple linear regression analysis, classical assumption test. The hypothesis was tested using the t test and f test. The results of this study indicate that entertainment tax revenue and advertisement tax have a significant effect on Deli Serdang Regency's original revenue in 2016-2020, this can be shown from the results of the F (simultaneous) test calculation, indicating that F-count > F-table (6,209 > 3.06) which means H_o is rejected and H_a is accepted. The coefficient of determination test of 0.209 or 20.9% can affect PAD.Keywords: Entertainment Tax, Advertisement Tax, Local Revenue